Research of LBS privacy preserving based on sensitive location diversity - Chang-li ZHOU; Chun-guang MA; Song-tao YANG (Tongxin xuebao)
Before getting location-based query service，constructing a cloaking region or picking an anchor which is still in a sensitive area is vulnerable to lead location privacy exposure.An algorithm of selecting anchor is proposed based on sensitive location diversity.By defining sensitive locations and filtering different ones according to users’ visiting number and peak time，locations with similar features are chosen to construct a diversity zone，and the centroid of the zone is chosen as an anchor that raises location diversity.Referring to SpaceTwist，a query algorithm (HINN) is proposed to get places of interest (PoI)，and query results can be inferred without providing any user’s actual location.The defect in SpaceTwist that PoIs are found around the anchor is modified，which improves querying accuracy.The experiments show that users’ location privacy is protected well when the user is staying at a sensitive place，and the method has good working performances.